Case of immediate hypersensitivity to beer. Issue 6 (12th December 2015) - Inoue, Tomoko; Yagami, Akiko; Shimojo, Naoshi; Hara, Kazuhiro; Nakamura, Masashi; Matsunaga, Kayoko
Abstract: We report here a case of immediate hypersensitivity to beer, in which a female patient developed angioedema of the eyelids shortly after consuming beer. In skin prick tests, the patient showed positive reactions to the base ingredients of beer, particularly malt and barley. The specific serum immunoglobulin E antibodies against barley and malt displayed weakly positive reactivity. To identify the immunoreactive antigens, malt and barley proteins were separated by 2‐D polyacrylamide gel electrophoresis and immunoreacted with the patient's serum. The results of mass spectrometric analysis revealed that the main antigen was a protein with similarity to protein z‐type serpin. Notably, the identified antigen had a molecular weight of 20–25 kDa, which is markedly smaller than that previously reported for protein Z4 (44 kDa). Taken together, these analyses indicate that a possible new antigen which belongs to the protein Z family elicits immediate hypersensitivity to beer.